2003
DOI: 10.1179/096797803225001632
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preparation method on sinterability and properties of nanocrystalline MgAl2O4and ZrO2-MgAl2O4materials

Abstract: toughened alumina.18 Zirconia is also known to exhibit excellent mechanical properties and superior fracture tough-Nanocrystalline MgAl 2 O 4 and ZrO 2 -MgAl 2 O 4 ness because of its unique phase transformations occurring powders were synthesised by combustion and convenover stress or temperature.19 According to Fujita et al., an tional solid state reaction routes. T he synthesised addition of 20 wt-%ZrO 2 to MgAl 2 O 4 followed by hot powders were processed, dry pressed, and sintered for pressing may increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 18 publications
5
25
0
Order By: Relevance
“…Nevertheless, both samples have similar microstructures with equi-axed grains which are tightly packed. These results are well comparable with those reported for the MAS materials in the literature (Ganesh et al 2003).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Nevertheless, both samples have similar microstructures with equi-axed grains which are tightly packed. These results are well comparable with those reported for the MAS materials in the literature (Ganesh et al 2003).…”
Section: Resultssupporting
confidence: 94%
“…In our earlier studies, a single-phase MAS was identified when a stoichiometric mixture of α-Al 2 O 3 and calcined caustic MgO was compacted by die-pressing (200 MPa) or by extrusion and calcined at 1350 • C for 1 h (Ganesh et al 2001(Ganesh et al , 2002b(Ganesh et al , 2003(Ganesh et al , 2004(Ganesh et al , 2005). In the present study, the mixture of raw materials was consolidated by TIG (Bergström 1994) from organicbased suspensions containing 40 vol.%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,17 In the previous papers, [18][19][20][21] we have evidenced certain advantages of the organic precursors method based on the thermal decomposition of the heteropolynuclear complex combination resulted from the oxidation reaction of 1,2-ethanediol by the metallic nitrates by comparison with other unconventional methods. The aim of this work consists in the synthesis of MgAl 2 O 4 , using this method and the accomplishment of a comparative study relative to sol-gel route and combustion method taking into consideration the advantages and disadvantages of that.…”
Section: Introductionmentioning
confidence: 95%